2021
DOI: 10.1177/09500170211045830
|View full text |Cite
|
Sign up to set email alerts
|

Thursday Night and a Sing-along ‘Sung Alone’: The Experiences of a Self-employed Performer During the Pandemic

Abstract: COVID-19 has had a devastating impact on those working in the UK’s creative economy, and particularly its entertainment sector. This article explores the experiences of Mark Godiva, a self-employed musician whose livelihood has been radically threatened by the virus and its associated restrictions. Mark’s story highlights both the continuities and challenges that have been created for those working on the front line of what is a dramatically altered cultural landscape. It illustrates the continuing precarity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In many ways, these findings from our study confirm the results from early research on the effects of the pandemic on creative industries regarding the increased struggle of sustaining one's artistic practice given the new circumstances (Banks and O'Connor 2021;Hancock et al 2021). Thus, the precarity of working conditions for cultural entrepreneurs was arguably exacerbated by the pandemic, pushing an already strained effort for resilience to the brink (Comunian and England 2020;Haynes and Marshall 2018).…”
Section: Artists Manoeuvring the Crisis: Insights From The Interviewssupporting
confidence: 82%
See 3 more Smart Citations
“…In many ways, these findings from our study confirm the results from early research on the effects of the pandemic on creative industries regarding the increased struggle of sustaining one's artistic practice given the new circumstances (Banks and O'Connor 2021;Hancock et al 2021). Thus, the precarity of working conditions for cultural entrepreneurs was arguably exacerbated by the pandemic, pushing an already strained effort for resilience to the brink (Comunian and England 2020;Haynes and Marshall 2018).…”
Section: Artists Manoeuvring the Crisis: Insights From The Interviewssupporting
confidence: 82%
“…Moving to online performance meant he had to invest more time into learning new songs, along with the extra time needed to set up his house for his recordings and the extra money invested into new recording equipment, all while earning less than he did before the lockdown. Hancock et al (2021) further explain how these effects also influenced the musician's mental health because without his act he could no longer be his on-stage persona. This can be contrasted with the findings of Jones (2022), who showed that the newfound situation with cancelled shows also meant artists could slow down in their work process, opening up for a period of reflection and remodelling how to approach their work.…”
Section: Cultural Entrepreneurship During the Covid-19 Pandemic: An E...mentioning
confidence: 96%
See 2 more Smart Citations
“…The pandemic has brought major disruption to the performing arts industry – an industry known for already precarious, often freelance, employment prior to the pandemic [4, 5] with professionals in the industry often unprotected by employment regulations and unable to plan for the future [6]. In early 2021 the Actors Fund, a non-profit organisation supporting the entertainment community in America, surveyed 7,163 creators and actors during the pandemic and found that 76% reported loss of income, 62% lost part-time or gig employment, and 50% lost full-time jobs [7].…”
Section: Introductionmentioning
confidence: 99%